Topical Skullcapflavone II attenuates atopic dermatitis in a mouse model by directly inhibiting associated cytokines in different cell types - Lee, Youngae; Oh, Jang-Hee; Li, Na; Jang, Hyun-Jae; Ahn, Kyung-Seop; Oh, Sei-Ryang; Lee, Dong Hun; Chung, Jin Ho (Frontiers in Immunology, 2022)
Skullcapflavone II (SFII), a flavonoid derived from Scutellaria baicalensis, is an anticancer agent. We aimed to validate SFII for atopic dermatitis (AD) therapy by demonstrating the anti-inflammatory effects of SFII in an AD mouse model produced by the topical application of the vitamin D3 analog MC903. We showed that topical treatment with SFII significantly suppressed MC903-induced serum IgE levels compared with topical hydrocortisone (HC) treatment. Topical SFII also prevents MC903-induced pruritus, skin hyperplasia, and inflammatory immune cell infiltration into lesional skin comparable to topical HC. In addition, MC903-induced immune cell chemoattractants and AD-associated cytokine production in skin lesions were effectively suppressed by topical SFII. The production of MC903-induced effector cytokines influencing T helper (Th)2 and Th17 polarization in lesioned skin is significantly inhibited by topical SFII. Furthermore, we showed that SFII can directly inhibit the production of AD-associated cytokines by human primary keratinocytes, mouse bone marrow-derived cells (BMDCs), and mouse CD4+ T cells in vitro. Lastly, we demonstrated that topical SFII more effectively suppressed serum IgE levels, the production of IL-4 and thymic stromal lymphopoietin (TSLP), and infiltration of CD4+ T cells and Gr-1+ cells (neutrophils) into lesion skin compared to topical baicalein (a flavonoid derived from Scutellaria baicalensis), which has anti-inflammatory effects. Taken together, our findings suggest that SFII may have promising therapeutic potential for this complex disease via the regulation of multiple AD-associated targets.